2020
DOI: 10.9734/ijtdh/2020/v41i2330417
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practices Related to COVID-19 Prevention among Health Care Workers in Sokoto Metropolis, Nigeria

Abstract: Aims: This study aims to assess the knowledge, attitude, and practices related to coronavirus pandemic among health care workers in Sokoto metropolis of Sokoto State, Nigeria.  Study Design: A cross-sectional study Place and Duration of Study: The study was conducted in Sokoto metropolis, northwest Nigeria between July and October 2020 Methodology: Four hundred and twenty-seven respondents were selected using a multi-stage sampling technique. Data were collected manually using a self-administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…The major preventive practices among the respondents in the present study were hand washing, wearing of face mask and use of hand sanitizer which was similar to what was reported in other studies in Nigeria, Ghana and Saudi Arabia. [22][23][24][25]27,29 In the present study, respondents agreed that apart from washing of hands, wearing of face masks and use of hand sanitizers that social distancing, selfisolation of infected person, avoidance of hand shake and avoid touching of nose, mouth and eyes are other means of preventing the spread of COVID-19. This was consistent with studies reported from Pakistan and China.…”
Section: Binary Logistic Regression Of Respondents' Characteristics and Covid-19 Preventive Practicesmentioning
confidence: 69%
See 4 more Smart Citations
“…The major preventive practices among the respondents in the present study were hand washing, wearing of face mask and use of hand sanitizer which was similar to what was reported in other studies in Nigeria, Ghana and Saudi Arabia. [22][23][24][25]27,29 In the present study, respondents agreed that apart from washing of hands, wearing of face masks and use of hand sanitizers that social distancing, selfisolation of infected person, avoidance of hand shake and avoid touching of nose, mouth and eyes are other means of preventing the spread of COVID-19. This was consistent with studies reported from Pakistan and China.…”
Section: Binary Logistic Regression Of Respondents' Characteristics and Covid-19 Preventive Practicesmentioning
confidence: 69%
“…24 The preventive practices towards COVID-19 among the respondents in the present study was high which was similar to what was reported in China and Pakistan but higher than other studies in Nigeria, Ghana and Bangladesh. [22][23][24]28,29,31,32 The respondents personal and environmental characteristics could account for the high preventive practices in this present study. The receptive attitude of the primary healthcare workers compare to tertiary healthcare workers could also account for the high preventive practices observed in the present study.…”
Section: Binary Logistic Regression Of Respondents' Characteristics and Covid-19 Preventive Practicesmentioning
confidence: 95%
See 3 more Smart Citations